2014
DOI: 10.26509/frbc-ec-201411
|View full text |Cite
|
Sign up to set email alerts
|

New Rules for Credit Default Swap Trading: Can We Now Follow the Risk?

Abstract: Credit default swaps, a useful but complex financial innovation of the 1990s, were traded over the counter before the financial crisis. Because of this infrastructure, a very opaque market emerged, and from it, the severe risk imbalances that helped fuel the crisis. Reforms are now being worked out and put in place which will move the majority of credit default swaps transactions to more transparent exchanges. Market participants will be able to see pre-trade and post-trade pricing, and regulators will have ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Concerns about the destabilizing effects of credit default swaps prompted policy reforms articulated in the Basel III Accord and in the U.S. codified in the Dodd‐Frank legislation (Carlson & Jacobson, 2014). These reforms were mainly aimed at improving transparency and reducing an excessive accumulation of risk by a single issuer 33 .…”
Section: Policies Affecting Individual Financial Institutionsmentioning
confidence: 99%
“…Concerns about the destabilizing effects of credit default swaps prompted policy reforms articulated in the Basel III Accord and in the U.S. codified in the Dodd‐Frank legislation (Carlson & Jacobson, 2014). These reforms were mainly aimed at improving transparency and reducing an excessive accumulation of risk by a single issuer 33 .…”
Section: Policies Affecting Individual Financial Institutionsmentioning
confidence: 99%
“…To address the opacity of over‐the‐counter (OTC) markets, the Dodd–Frank Act requires four primary actions to improve market transparency. Carlson and Jacobson (2014) observed that the regulation does not effectively alter incentives for systemically important financial institutions (SIFI) to become too big to fail. It remains to be seen if risk is being transferred to those capable of absorbing that risk in a crisis.…”
Section: Introductionmentioning
confidence: 99%
“…The regulation of the CDS market is thus a relevant policy issue and some regulatory efforts have been made in the aftermath of the financial crisis. In particular, the G-20 agreed to reforms at their August 2009 meeting that were subsequently codified in the United States in the Dodd-Frank legislation (Carlson and Jacobson, 2014). These reforms were mainly aimed at improving transparency and avoiding excessive accumulation of risk by a single CDS issuer (e.g., the American Insurance Group).…”
Section: Introductionmentioning
confidence: 99%